Strategi Marketing Communication dalam Kolaborasi antara Novotel Jakarta Gajah Mada dan Food Cycle - Saputra, Andien Putri Aliffia; Nugroho, David Rizar (Jurnal EMT KITA, 2025)
Food waste management presents a complex challenge in the hospitality industry, requiring innovative and collaborative solutions. This study aims to identify factors influencing the effectiveness of communication and marketing strategies within the collaboration between Novotel Jakarta Gajah Mada and Food Cycle to reduce food waste, enhance corporate image, and generate social impact. The marketing strategy is analyzed using the 4Ps marketing mix framework (product, price, place, promotion), while the effectiveness of digital communication is evaluated based on the quality of educational content, community engagement, and campaigns featuring the Green Key logo as a symbol of waste management. A descriptive qualitative method was employed, with data collected through observation, interviews, active participation, and literature review. Findings reveal that Novotel’s leftover food is distributed by Food Cycle to underprivileged communities and processed into organic fertilizer, while Novotel supports sustainability by purchasing food supplies from Food Cycle. Key challenges include fluctuations in waste volume and limited resources. This study integrates marketing mix theory and digital communication as a cross-sector collaboration model for sustainability in Indonesia’s hospitality industry.
Keywords: Marketing Communication; Food Waste; Hotel; Sustainability; Collaboration